PENGARUH FILLER ABU SEKAM PADI TERHADAP CAMPURAN AC-WC UNTUK DAERAH PESISIR PANTAI - farida, ida; Juniayanti, Santika (Jurnal Jalan Jembatan, 2024)
Waterlogging can cause damage to paved pavement construction, especially roads in coastal areas that experience seawater inundation by tidal water. Thus, it is necessary to innovate the paved mixture by optimizing natural materials or rice husk ash waste in the asphalt mixture. The purpose of the study was to obtain the stability and fatigue value of the use of rice husk ash filler in the AC-WC mixture in coastal areas. The research method uses experimental methods. The research phase consisted of testing the quality of the material, determining KAO, and soaking with seawater for 24 hours on a filler mixture with rice husk ash using a composition of 6.5%, 7%, and 7.5%, and Marshall testing was carried out. The results showed a decrease in the stability value from typical asphalt of 1856.6 kg to a mixture of rice husk ash of 1346.2 kg. However, there was an increase in the stability value and the percentage of rice husk ash filler. Rice husk ash has a content that can add stability value, increasing flow from 2.02 mm of typical asphalt to 2.7 mm for rice husk ash content of 7%. However, there is a decrease if the percentage of rice husk ash is increased to 7.5%. The higher the percentage of filler with rice husk ash will affect the decrease in flow value. The Marshall Quotient value decreased from the normal asphalt value of 946.17 kg/mm to 543.64 kg/mm and increased by a percentage of 7%-7.5% with a value of 1133.21 kg/mm. The increase in the number of rice husk ash fillers further increases the Marshall Quotient value, but the flow value decreases because the specific gravity of rice husk ash is higher than that of fine aggregate, so that the asphalt covering the aggregate becomes thinner and fatigue decreases. The next step needs to be to conduct a durability test check related to the durability level of the AC-WC Asphalt mixture with rice husk ash. Field-scale applications that can increase the Marshall Quotient value are used a mixture of husk ash filler by 7%-7.5%. Keywords: AC-WC, filler, Marshall, rice husk ash, sea water